Stress-Strain-Sorption Behaviour of Smectites Upon Exposure to Dry and Wet CO2 - Zhang, Miao; Spiers, Christopher James; Liu, Jinfeng; Zhou, Hongwei (Frontiers in Earth Science, 2022)
The swelling-shrinkage behavior of smectites induced by interlayer uptake or sorption of CO2 and H2O has been investigated with increasing interest recent years, primarily because of its potential impact on the sealing efficiency of clay-bearing caprocks overlying CO2 storage reservoirs. To get a better understanding of the stress-strain-sorption coupling in smectite exposed to supercritical CO2, we performed multiple stepwise axial loading and unloading, oedometer-type experiments on ~1mm thick discs of pre-pressed Na-SWy-1 and of Ca-SAz-1 montmorillonite. Initially air-dry (AD) samples were first tested in the presence of wet CO2 (20% RH) at 10MPa pressure, and in the vacuum-dry (VD) state in the presence of pure (dry) CO2 at 10MPa. The samples were incrementally loaded and unloaded at 40°C, employing effective axial stresses ranging from 0.5–44MPa. Control tests using wet and dry He or Ar instead of CO2, were performed to distinguish strains due to loading-related CO2 sorption/desorption from purely poroelastic effects. All samples saturated with CO2 exhibited 30-65% lower apparent stiffness moduli than when saturated with He or Ar, showing that CO2 adsorption/desorption altered the mechanical response of pre-pressed smectites. Relative to the He and Ar tests, swelling strains of a few % (corrected for poroelastic effects) were measured for AD Na-SWy-1 smectite exposed to wet CO2, decreasing from 4.9% to 3.8% with increasing effective axial stresses in the range 1.6 –36.2 MPa. AD SAz-1 material exhibited similar tends. VD samples tested with dry CO2 showed much smaller relative swelling strains (0.5–1.5%), which also decreased with increasing applied effective stresses. The experimental data on relative swelling strain versus effective stress are well fitted by a recent thermodynamic model for stress-strain-sorption behavior in coal. Results derived from model fits indicate that smectite-rich rocks have significant storage capacity for CO2 at shallow depths (up to 1.5–2 km) through CO2 sorption by the clay minerals. However, this component of storage capacity is reduced by more than 80% with increasing burial depth beyond 3 km. The model provides a first step towards modelling stress-strain-sorption effects in smectite rich caprocks penetrated by CO2, though further refinements are needed for broader application to the smectite-CO2-H2O system.